Fast Diffusion of Multivalent Ions Facilitated by Concerted Interactions in Dual‐Ion Battery Systems. Issue 27 (9th August 2018) - Li, Hongyi; Okamoto, Norihiko L.; Hatakeyama, Takuya; Kumagai, Yu; Oba, Fumiyasu; Ichitsubo, Tetsu
Abstract: Sluggish solid‐phase diffusion has been an essential issue in developing intercalation electrode materials using multivalent ions. Compared to monovalent Li ions, the diffusion of multivalent ions is still not well understood. Here, combining first‐principles calculations with electrochemical experiments, it is shown that the diffusion of divalent Mg ions is significantly facilitated in Li–Mg dual‐ion systems, and the activation energy is remarkably reduced by the concerted interactions of the preceding Li ions and following Mg ions. Thus, making dual‐ion systems is a promising way to construct high‐energy‐density, rechargeable batteries with multivalent ions. This work will provide a new perspective on solid‐phase diffusion that is typically a rate‐controlling process in battery systems and fuel cell devices. Abstract : Concerted interaction of Li–Mg dual ions in solid‐phase diffusion process is both experimentally and computationally investigated using, as an example, a Mo6 S8 sample cathode. This concerted interaction can significantly facilitate the diffusion of multivalent ions, which can overcome the essential issue hindering the development of high‐performance rechargeable batteries with multivalent ions.